Implementasi kurikukum merdeka belajar di SMK Pusat Keunggulan - Nanang Setiawan; Herminarto Sofyan (Jurnal Taman Vokasi, 2022)
The independent learning curriculum is a prototype curriculum that has currently been implemented in 2500 activator schools and 901 SMK Centers of Excellence (SMK PK). This study aims to describe the findings of scientific journal articles regarding the implementation of the independent learning curriculum at SMK PK through a literature review. This research is expected to be a reference and consideration for policymakers to make improvements and socialization to other vocational schools so that they can implement the independent learning curriculum well and efficiently. Searching for research journal data using a database from Google Scholar by applying the keywords "free learning at SMK" and "Vocational PK curriculum." Journal articles are limited to those published since 2021, but there are no restrictions on the use of language or the research methodology used. In this literature study, 14 articles have been screened by authors. The results of this study indicate that the independent learning curriculum policy is indeed still in the development stage and field testing before it is actually implemented in all schools at every level by the government. However, all PK Vocational Schools that have implemented this curriculum welcome it enthusiastically, although some still have obstacles in its implementation.